Multi-symptom measurement based fault detection of the PEM fuel cell system - Polak, Adam; Kluczyk, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The proper functioning of the fuel cell system depends on the proper operation of all its subsystems. One of the key subsystems is the oxidant supply system, which is responsible for supplying oxygen for the electrochemical reaction taking place in the cell. It also transports the reaction products, i.e., water, outside the fuel cell stack, and in some cases removes excess heat generated in the stack. Changes in the technical condition of machine individual elements always result in changes in operating or residual parameters; however, it is necessary to select appropriate diagnostic methods to be able to use these changes to assess the machine`s technical condition.
Keywords: PEM fuel cells; failure detection; oxygen starvation; cell flooding; acoustic emission; vibrations